Perbedaan Tingkat Konsumsi Protein,Vitamin C, Besi, dan Seng pada Remaja Putri yang Anemia dan Tidak Anemia di Asrama SMA MTA Surakarta - Hibdiyah, Eva, Endang Nur Widyaningsih, S.ST.,M.Si,Med, Susi Dyah Puspowati, M.Si (2013)
Background: Adolescents are vulnerable to nutrition probelms, one nutritional problem that often occurs in adolescents is anemia. One of cause of anemia is the low intake of nutrients, especially iron. Several nutrients that affect the formation of haemoglobin are protein, vitamin C, iron and zinc. Objective: This study aimed to determine the differences of the level of consumption of protein, vitamin C, iron and zinc in adolescent girls who were anemic and non anemic at female dorm of MTA Surakarta. Method: The research was an observational research with cross secsional approach. The respondents of this study were 75 young women lived in the dormitory. Data were analyzed by Independent Sample Test for data consumption of protein, vitamin C, zinc and Mann Whitney test for iron consumption data. Result: The results showed that most anemic girls had sufficient protein (70%) but insufficient vitamin C (63,2%), iron and zinc (97,9%). Based on the statistical analyzes, there was not any difference of protein (p = 0.729) and vitamin C (p = 0.114) comsumption between two groups. Meanwhile, there was difference of iron (p = 0.034) and zinc (p = 0.043) consumption between two groups. Conclusion: There was not any difference between the levels of protein and vitamin C intake in adolescent girls who were anemic and non anemic. There was difference between the level of iron and zinc intake in adolescent girls who were anemic and non anemic.